2003
DOI: 10.1679/aohc.66.17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of BDNF and TrkB in mouse taste buds after denervation and in circumvallate papillae during development.

Abstract: BDNF (brain-derived neurotrophic factor) is a member of the neurotrophin family which affects the proliferation and survival of neurons. Using an immunocytochemical method, we examined the expression of BDNF and its receptor, TrkB, in the taste bud cells of the circumvallate papillae of normal mice and of mice after transection of the glossopharyngeal nerves. We additionally observed the expression of BDNF and TrkB in the developing circumvallate papillae of late prenatal and early postnatal mice. In normal un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…However, substantial differences exist between their study and ours in terms of colocalization and taste cell types. For example, Uchida et al (2003) report that BDNF and trkB are mainly absent from N-CAM-LIR type III taste cells, whereas we consistently find BDNF localized to type III taste cells (Yee et al, 2003). Their report is based on immunocytochemistry utilizing the same antiserum that we employ.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, substantial differences exist between their study and ours in terms of colocalization and taste cell types. For example, Uchida et al (2003) report that BDNF and trkB are mainly absent from N-CAM-LIR type III taste cells, whereas we consistently find BDNF localized to type III taste cells (Yee et al, 2003). Their report is based on immunocytochemistry utilizing the same antiserum that we employ.…”
Section: Discussionmentioning
confidence: 80%
“…However, in hamsters, unlike the case in mice, taste buds do not completely disappear following denervation; hence, the expression of neurotrophins may differ between these species. For mice, Uchida et al (2003) found that trkB is present in nerve fibers following nerve transection, but did not find BDNF in nerve fibers, and the authors do not discuss NGF or its high-affinity receptor, trkA, or the proneurotrophin receptor p75 in mouse taste buds (Uchida et al, 2003). Similarly, Fan et al (2004) described the presence of p75 and NT3 in taste epithelia.…”
mentioning
confidence: 99%
“…Both mRNA and protein of BDNF (brain-derived neurotrophic factor), another neurotrophic factor and a member of the NGF (nerve growth factor) family, were detected in taste bud cells (Nosrat et al, 1996b;Yee et al, 2003;Uchida et al, 2003). NGF and NT-3 (neurotrophin-3), also members of the NGF family, were likewise found in taste bud cells (Chou et al, 2001;Ganchrow et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The degenerated taste buds and nerve fibers disappear from the circumvallate and foliate papillae in rodents (Hosley et al 1987;Suzuki et al 1996). Concomitant with the structural loss of taste buds and nerve fibers is a loss of immunoreactivity of substances such as neural cell adhesion molecule (NCAM), brain-derived neurotrophic factor (BDNF), nerve growth factor, and glial cell line-derived neurotrophic factor normally found in taste bud cells (Takeda et al 1999(Takeda et al , 2005Uchida et al 2003;Yee et al 2005). After regenerated nerve fibers appear in the trench wall epithelium, taste buds regenerate, and the immunoreactivity of the above substances also reappears, indicating that the expression of these substances is dependent on innervation.…”
Section: Introductionmentioning
confidence: 99%